Heritage conservation in postcolonial India : approaches and challenges - Chalana, Manish; Krishna, Ashima (Abingdon, Oxon ; New York : Routledge, 2021)
"Heritage Conservation in Postcolonial India seeks to position the conservation profession within historical, theoretical, and methodological frames to demonstrate how the field has evolved in the post-colonial decades and follow its various trajectories in research, education, advocacy, and practice. Split into four sections, this book covers important themes of institutional and programmatic developments in the field of conservation; critical, and contemporary challenges facing the profession; emerging trends in practice that seek to address contemporary challenges; and sustainable solutions to conservation issues. The cases featured within the book elucidate the evolution of heritage conservation profession, clarifying the role of key players at the central, state, and local level, and considers intangible, minority, colonial, modern and vernacular heritages among others. This book also showcases unique strands of conservation practice in the postcolonial decades to demonstrate the range, scope, and the multiple avenues of development in the last seven decades. An ideal read for those interested in architecture, planning, historic preservation, urban studies, and South Asian studies"--
Developments in Heritage Conservation: Institutions and Programs. The Evolving Role of India's Foremost Heritage Custodian: Archaeological Survey of India / Saptarshi Sanyal -- Critical Challenges in Heritage Conservation -- Emerging Trends in Heritage Conservation. Conserving vernacular heritage of minority groups in Malabar, Kerala / Patricia Tusa Fels -- Sustainable Approaches to Heritage Conservation. Community led sustainable and responsible tourism promoting intangible cultural heritage of West Bengal / Ananya Bhattacharya.
Includes bibliographical references and index.
Keywords: Historic preservation -- India; Cultural property -- Protection -- India